2010
DOI: 10.1042/bj20100129
|View full text |Cite
|
Sign up to set email alerts
|

A novel HPLC-based approach makes possible the spatial characterization of cellular PtdIns5P and other phosphoinositides

Abstract: SYNOPSIS Phosphatidylinositol-5-phosphate (PtdIns5P) was discovered in 1997 (Rameh, L.E.; Tolias, K.F.; Duckworth, B.C. and Cantley, L.C. 1997, Nature 390, 192–196) but very little is known about its regulation and function. Hitherto, studies of PtdIns5P regulation have been hindered by the inability to measure cellular PtdIns5P using conventional HPLC, owing to poor separation from PtdIns4P. Here we present a new HPLC method for resolving PtdIns5P from PtdIns4P, which makes possible accurate measurements of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
173
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(180 citation statements)
references
References 35 publications
7
173
0
Order By: Relevance
“…3 B and C). Consistent with the idea that adult body size in insects is predetermined during larval development we observed that newly eclosed adult dPIP4K 29 flies weighed less than the wild-type controls (Fig. 3H).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…3 B and C). Consistent with the idea that adult body size in insects is predetermined during larval development we observed that newly eclosed adult dPIP4K 29 flies weighed less than the wild-type controls (Fig. 3H).…”
Section: Resultssupporting
confidence: 74%
“…This revealed that PI5P levels in dPIP4K 29 were twice that measured in wild-type controls (Fig. 2D); by contrast, the levels of PI4P (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Just like other phosphoinositides, PtdIns(5)P also has its own subcellular locations. The majority of PtdIns(5)P is localized in the plasma membrane, while the minor part is in Golgi and Sarco/endoplasmic reticulum (SER) markers (57,58). It has been suggested that PtdIns(5)P plays crucial roles in cellular signaling pathways, although the corresponding functional role needs to be well defined (46).…”
Section: Phosphoinositides: Minor But Of Importancementioning
confidence: 99%